Role of Magnetic Resonance Spectroscopy in Supratentorial Brain Lesions - Rubab Qadir, Lal Rehman, Iram Bokhari, Rukan Alamuddin Shah, Arfa Qasim, Yousrah Atiff Arooqi, Mohammad Hasan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To identify the specificity and the sensitivity of MRS in diagnosing supratentorial brain lesions and will help the surgeons to rely on the respective diagnostic modality Method: A cross-sectional study was conducted in the Neurosurgery Department, at Jinnah Postgraduate Medical Center. The patients with conventional MR imaging showing space-occupying lesions which show a malignant diffusion restriction and enhancement were included. The histopathological diagnosis and the metabolites of the brain were detected by MR Spectroscopy were recorded. To find the association of the ratios of the brain metabolites, the chi-square test was used where a p-value of <0.05 was considered significant. The sensitivity and specificity of the MRS were evaluated then. Result: Overall, 112 patients were included in our study. 76(67.9%) patients were male. Headache (34.8%) was found to be the most common symptom. 39(34.8%) patients were diagnosed with Oligodendroglioma on histopathology. The Cho/Cr ratio >2 was found in 70(82.4%) patients diagnosed with neoplastic lesions. In 62(72.9%) patients diagnosed to have a neoplastic lesion on histopathology reported increased lipid peak and 67(78.8%) with the neoplastic lesion showed to have increased Cho/NAA ratio on MRS. The Cho/Cr ratio was found to be significantly associated with the neoplastic lesions with a significant p-value of <0.001. The MRS was determined to be 82.4% sensitive and 70.4% specific in the diagnosis of supratentorial brain lesions. This study will be quite beneficial as it will help surgeons rely on the more accurate method of diagnosing brain lesions and provide an outlook of a non-invasive method to diagnose the lesions. Conclusion: The study concludes that MRS has high diagnostic accuracy in diagnosing neoplastic and inflammatory lesions and is Keywords: Spectroscopy, brain lesions, medical resonance imaging